2009
DOI: 10.1007/s11192-008-2074-z
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and publication: How collaborative are scientists in South Africa?

Abstract: Using bibliographic records from the Science Citation Index, the paper examines the publication of South African scientists. The analysis shows that collaboration research in South Africa has been growing steadily and the scientists are highly oriented towards collaborative rather than individualistic research. International collaboration is preferred to domestic collaboration while publication seems to be a decisive factor in collaboration. The paper also looks at the collaboration dimensions of partnering co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 39 publications
(32 reference statements)
2
43
0
2
Order By: Relevance
“…Whereas the presence of the UK and France can be attributed to their colonial legacies in Africa [21], the role of Italy, the US and Sweden might be related to funding some research conducted in the region, hence their collaboration with countries in SSA. These countries, among others, have been regarded as key international collaborators in research on various topics in SSA (see [29], [38]). Sooryamoorthy [38] observes that South African scientists largely collaborate with their counterparts from the US, the UK, Germany, Australia, Canada, France, the Netherlands, Italy, Belgium, Israel, Scotland, Switzerland, Japan, Sweden and Spain.…”
Section: Distribution Of Data Records By Countries Of Author Affiliationmentioning
confidence: 99%
“…Whereas the presence of the UK and France can be attributed to their colonial legacies in Africa [21], the role of Italy, the US and Sweden might be related to funding some research conducted in the region, hence their collaboration with countries in SSA. These countries, among others, have been regarded as key international collaborators in research on various topics in SSA (see [29], [38]). Sooryamoorthy [38] observes that South African scientists largely collaborate with their counterparts from the US, the UK, Germany, Australia, Canada, France, the Netherlands, Italy, Belgium, Israel, Scotland, Switzerland, Japan, Sweden and Spain.…”
Section: Distribution Of Data Records By Countries Of Author Affiliationmentioning
confidence: 99%
“…More recently, a number of such studies include developing countries in general (Arunachalam and Viswanathan 2008) and African countries (Boshoff 2009;Sooryamoorthy 2009) in particular. Sooryamoorthy (2009) investigated the collaboration patterns of South African researchers and Boshoff (2010) identified the collaborative patterns in the Southern African development community (SADC) countries. Onyancha and Maluleka (2011) found out that knowledge production through collaborative research among sub-Saharan African countries is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Onyancha and Ocholla (2007, p. 239) observe that research collaboration is beneficial in that it enables researchers to share knowledge, skills and techniques; it makes it possible to transfer tacit knowledge; it provides intellectual companionship; it plugs the researcher into a wider network of contacts in the scientific community; and it enhances the potential visibility of a work as well as reducing the costs of research. Abramo et al (2009), Frenken (2002 and Sooryamoorthy (2009) have also observed that collaborative research not only leads to an increase in knowledge production but also encourages knowledge sharing among the participating researchers. Klitkou et al (2009, p. 2) opine that ''project cooperation between research institutions, industry and long-term partnerships in networks of excellence where industry and research institutions pool their resources, and improved knowledge transfer between public research and industry contribute effectively to the effective knowledge sharing between public science and industry''.…”
mentioning
confidence: 99%